2014
DOI: 10.1039/c3lc50991e
|View full text |Cite
|
Sign up to set email alerts
|

Biosensor design based on Marangoni flow in an evaporating drop

Abstract: Effective point-of-care diagnostics require a biomarker detection strategy that is low-cost and simple-to-use while achieving a clinically relevant limit of detection. Here we report a biosensor that uses secondary flows arising from surface Marangoni stresses in an evaporating drop to concentrate target-mediated particle aggregates in a visually detectable spot. The spot size increases with increasing target concentration within the dynamic range of the assay. The particle deposition patterns are visually det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
70
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 30 publications
0
70
0
Order By: Relevance
“…and comparable to a very sensitive (0.006 p.p.m.) approach to gliadin determination recently described in literature 30 , thus opening the way to highsensitive detection.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…and comparable to a very sensitive (0.006 p.p.m.) approach to gliadin determination recently described in literature 30 , thus opening the way to highsensitive detection.…”
Section: Resultsmentioning
confidence: 99%
“…Last, but not least, is the time scale of the analysis that, when operating at low concentrations, is mainly around half an hour or more 6,11 . Very recently, alternative techniques have been proposed for concentrating analytes, but still using the passive effects of the evaporation behaviour of sessile droplets [30][31][32] .…”
mentioning
confidence: 99%
“…176,177 The OCT has helped to usher in a new era of in vivo diagnostic imaging. 178 Trantum et al 179 reported a biosensor that used secondary flows arising from surface Marangoni stresses that are necessary to produce signal in the proposed design. These evaporation-driven flows generate signal in the assay based on a polydimethylsiloxane substrate but not substrates with greater thermal conductivity like indium tin oxidecoated glass.…”
Section: Optical Biosensorsmentioning
confidence: 99%
“…In this proof-of-concept design, the M13K07 bacteriophage was used as a model target. 179 Lee et al 180 described a unique system integrating several optoelectronic-based biological diagnostic tools such as an ellipsometer, a laser Doppler vibrometer/interferometer, SPR analyzer, an interference microscope, a photon tunneling microscope, an optical coherence tomography unit, and a confocal scanning microscope. This OBMorph system, useful as a powerful optical metrology diagnostic tool, can be used at the beginning of sensor chip fabrication, during the signal detection/monitoring, and in the final biological analysis.…”
Section: Optical Biosensorsmentioning
confidence: 99%
“…A number of new portable microfluidic devices were reported [9] with many built-in functions for creating simpler ones [10], faster and cheaper devices [11] with better detection limits. Microfluidic device consisting of 500 channels is intended for the rapid analysis (within 20 minutes) of the integrity of the sperm DNA using fluorescent imaging [11].…”
Section: Introductionmentioning
confidence: 99%